Strategi Peningkatan Kinerja Sekolah SMA Berbasis Balanced Scorecard Pada Yayasan Pendidikan Madania Indonesia - Daud, Muallim; Rahim, Anwar; Kohar, Abdul (Jurnal Manajemen, 2018)
Performance improvement strategy is a method to find new techniques in solving problems faced by organization and improve its performance. This is a quantitative research in a descriptive design, the chosen sample are 95 students of 11 and 12 graders as the perspective of customers, 44 teachers and employees as the perspective of learning and growth. This study aims to measure SMA Madania’s performance using balanced scorecard, analyzing the main strategy that SMA Madania has to improve. Analyzing the targeted strategy that has become SMA Madania’s priority to realize vision, mission, and organization goals. Analyzing the performance standard that can be implemented to measure the achievement of targeted strategy conducted by SMA Madania. The measurement has been done on four perspectives of balanced scorecard; financial, customers, internal business process, and SMA Madania’s learning and growth. The results showed: finances were managed economically, effectively and efficiently in 2013 – 2015. Customer’s aspect has shown in the level of satisfaction (student) on a scale of 70 per cent scored 4 (satisfied). Internal Business Process’ aspects such as innovation, business process, and after sales services (alumni) scored 48 per cent (very good). Learning and growth’s aspect shown employees’ satisfaction 42.71 per cent on a scale of 2 (unsatisfied). Based on SWOT analysis, Balanced Scorecard recommended some strategies, finance performance improvement through billings and savings, rejuvenation of facilities and infrastructure, and compensation improvement for employees and employees’ retention, mapping and re-planning of human resources for the appropriate department and function in accordance with competencies and qualifications.